Understanding the Academic Significance of World Value Survey - Gar, Ruqayya, Aminu; Umar, Mohammed, Nuru; Muhammad, Murtala (My University, 2022)
Measuring socio-economic and political value change needs a simple and valid interpretation at both collective and individual levels. However, surveys dealing with value change are limited and defective. This article aims on World Value Survey (WVS) and its academic significance in the study of political behavioural change in Bauchi state Nigeria 1999-2016, through, a qualitative method of data collection and analysis. Conclusion suggests that as a prominent and well-established academic source of data, the WVS instruments, and data are significant for the analysis of the changing political behaviour in Bauchi State. Considering that, the study centres only on the part of the WVS survey data on two dimensions of political behaviour: (1) formal political participation and (2) extra parliamentary activism. These two dimensions comprise nine values which include interest in politics, voting, protests, demonstrations, confidence in political parties, parliament, government, leadership and quality preferences randomly selected and adopted The adoption of these two important segments of the WVS data helped the analysis processes particularly in examining the trends and patterns of the changes in political behaviour as component of democratic attitude and value. WVS is also a means through which governments and its agencies will be influenced to make authoritative decisions (policies) for the continuity and democratic development.
Keywords: Academic Significance; Bauchi; Democratic Attitude; Nigeria; Political Behavioural Change; World Value Survey